Urine soluble TLR4 levels may contribute to predict urinary tract infection in children: the UTILISE Study - ALPAY, HARİKA; YILDIZ, NURDAN (My University, 2023)
Background: One of the most common bacterial infections in childhood is urinary tract infection (UTI). Toll-like receptors (TLRs) contribute to immune response against UTI recognizing specific pathogenic agents. Our aim was to determine whether soluble TLR4 (sTLR4), soluble TLR5 (sTLR5) and interleukin 8 (IL-8) can be used as biomarkers to diagnose UTI. We also aimed to reveal the relationship between urine Heat Shock Protein 70 (uHSP70) and those biomarkers investigated in this study. Methods: A total of 802 children from 37 centers participated in the study. The participants (n = 282) who did not meet the inclusion criteria were excluded from the study. The remaining 520 children, including 191 patients with UTI, 178 patients with non-UTI infections, 50 children with contaminated urine samples, 26 participants with asymptomatic bacteriuria and 75 healthy controls were included in the study. Urine and serum levels of sTLR4, sTLR5 and IL-8 were measured at presentation in all patients and after antibiotic treatment in patients with UTI. Results: Urine sTLR4 was higher in the UTI group than in the other groups. UTI may be predicted using 1.28 ng/mL as cut-off for urine sTLR4 with 68% sensitivity and 65% specificity (AUC = 0.682). In the UTI group, urine sTLR4 levels were significantly higher in pyelonephritis than in cystitis (p < 0.0001). Post-treatment urine sTLR4 levels in the UTI group were significantly lower than pre-treatment values (p < 0.0001). Conclusions: Urine sTLR4 may be used as a useful biomarker in predicting UTI and subsequent pyelonephritis in children with UTI. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; TLR4; Toll-like receptor 4; Urinary tract infection; UTI; UTILISE study